Norm elicitation in within-subject designs: testing for order effects - D’Adda, Giovanna; Drouvelis, Michalis; Nosenzo, Daniele (Elsevier, 2016)
We investigate norms of corruption using the norm-elicitation procedure introduced by Krupka and Weber (2013). We use a within-subject design whereby the norms are elicited from the same subjects who are observed making choices in a bribery game. We test whether the order in which the norm-elicitation task and the bribery game are conducted affects elicited norms and behavior. We find little evidence of order effects in our experiment. We discuss how these results compare with those reported in the existing literature.